2018
DOI: 10.3389/fneur.2018.00044
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma Chemokines for Eosinophils in Neuromyelitis Optica Spectrum Disorders during Remission

Abstract: BackgroundA prominent pathological feature of neuromyelitis optica spectrum disorders (NMOSD) is markedly greater eosinophilic infiltration than that seen in other demyelinating diseases, like multiple sclerosis (MS). Eosinophils express the chemokine receptor CCR3, which is activated by eotaxins (CCL11/eotaxin-1, CCL24/eotaxin-2, CCL26/eotaxin-3) and CCL13 [monocyte chemoattractant protein (MCP)-4]. Moreover, CCL13 is part of the chemokine set that activates CCR2. The present study aimed to evaluate plasma le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 42 publications
2
11
1
1
Order By: Relevance
“…It is also known as macrophage inflammatory protein 4α, and it primarily plays a role in the regulation of eosinophils and T cells (9,10). Studies have confirmed that CCL26 can block the CCL2 response and CCL26 regulates the proportion of CD4 + CD25 + FOXP3 + Tregs and the production of inflammatory factors in peripheral blood mononuclear cells following acute ischemic stroke via the STAT5 pathway that specific molecules, such as pro-inflammatory cytokines, including interleukin (IL)-4, tumor necrosis factor (TNF)-α, IL-1β and interferon-γ can promote the synthesis of CCL26 in human monocytes (11)(12)(13). Thus, CCL26 is of utmost importance to the regulation of inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%
“…It is also known as macrophage inflammatory protein 4α, and it primarily plays a role in the regulation of eosinophils and T cells (9,10). Studies have confirmed that CCL26 can block the CCL2 response and CCL26 regulates the proportion of CD4 + CD25 + FOXP3 + Tregs and the production of inflammatory factors in peripheral blood mononuclear cells following acute ischemic stroke via the STAT5 pathway that specific molecules, such as pro-inflammatory cytokines, including interleukin (IL)-4, tumor necrosis factor (TNF)-α, IL-1β and interferon-γ can promote the synthesis of CCL26 in human monocytes (11)(12)(13). Thus, CCL26 is of utmost importance to the regulation of inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%
“…Huber et al (2018) reported that during the relapse phase, CCL-11 may be downregulated, while during the secondary progressive phase, CCL-11 is upregulated to achieve plateau levels [ 40 ]. In other studies, it was detected that CCL-11 (and CCL-5) may discriminate clinical subtypes of multiple sclerosis [ 76 , 77 , 78 ]. Thus, both CCL-11 and CCL-5 were lowered during the inflammatory phase as compared with progressive multiple sclerosis [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…In other studies, it was detected that CCL-11 (and CCL-5) may discriminate clinical subtypes of multiple sclerosis [ 76 , 77 , 78 ]. Thus, both CCL-11 and CCL-5 were lowered during the inflammatory phase as compared with progressive multiple sclerosis [ 77 ]. Michael et al (2013) identified important chemokine profile markers including CCL-11 in patients with Neuromyelitis Optica (NMO), which were additionally different from those with MS [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Цитокины -семейство полипептидных молекул, которые синтезируются клетками различных тканей организма, наиболее активными продуцентами этих молекул являются иммунокомпетентные клетки. ЦК регулируют ряд нормальных физиологических функций, защитные реакции при внедрении различных патогенов, а также развитие большинства патологических процессов, включая канцерогенез, сердечно-сосудистые нарушения, аутоиммунную патологию, аллергические реакции и другие [4,31,40,49]. В отношении регуляции воспалительного процесса ЦК разделяют на провоспалительные (инициирующие и усиливающие воспалительную реакцию) и противовоспалительные (подавляющие воспаление).…”
Section: цитокины при ювенильных артритахunclassified